Capitalizing on Pakistan’s Public Diplomacy: Potential in Pursuit of Soft Power - Ashraf, Iqra (Journal of Pakistan Administration, 2024)
This paper examines Pakistan’s challenges in leveraging its soft power potential through effective public diplomacy (PD). It explores the root causes of Pakistan’s negative image perception, primarily from domestic economic, political, and social conditions. The study highlights the need for strategic policy investments to promote a tolerant, liberal, and multicultural ethos essential for strengthening Pakistan’s soft power toolkit. The research identifies several key obstacles, including the limited space for liberal arts in a conservative society, a lack of understanding of PD within policy circles and society, a prevailing mindset that views PD as tangential to core diplomatic functions, and insufficient expertise in executing PD activities among Foreign Ministry officers. The paper argues for a long-term, institutionalized approach to image-building, acknowledging that there are no quick fixes for long-held negative perceptions. It emphasizes the necessity of developing a comprehensive understanding of PD’s importance and potential impact. Through critical evaluation of existing policies and practices, this study aims to chart a course forward for Pakistan to effectively utilize its soft power resources and improve its global image through strategic public diplomacy efforts.